The Impact of Covid-19 on Household Consumption Expenditure in South Africa: A Macroeconomic Perspective: Impact of Covid-19 on Households' Consumption in South Africa - Oluwatayo, Isaac; Chimeri, Remembrance (The European Journal of Applied Economics, 2022)
The study was motivated by how the Coronavirus (Covid-19), potentially, affected household spending in South Africa. This is because, firstly, final consumption expenditure by households accounts for the largest share of Gross Domestic Product (GDP) in South Africa, and therefore a significant driver for economic growth. Secondly, expenditure by households is often used as a proxy of ascertaining the standard of living. The analysis drew data from the Household and Income and Expenditure Survey (HEIS), focussing on the period between 2010 and 2020. The results show that the Covid-19 pandemic had a negative impact on disposable income growth and spending of households at a macro-level. Coupled with other triggers, the contraction of the local economy resulted in job losses, with the unemployment level rising above 30% since the third quarter of 2020.
Keywords: Consumption expenditure, Covid-19, Economic growth, Households, South Africa